Maturity assignment based on histology‐validated macroscopic criteria: Tackling the stock decline of the Mediterranean swordfish (Xiphias gladius). Issue 2 (28th November 2019) - Marisaldi, Luca; Basili, Danilo; Candelma, Michela; Sesani, Vittoria; Pignalosa, Paolo; Gioacchini, Giorgia; Carnevali, Oliana
Abstract: Effective stock assessment relies on the evaluation of the reproductive potential of a population, but this is often achieved using fast, inexpensive, and inaccurate macroscopic indicators of gonadal maturity. Indeed, this approach suffers from high error rates as a result of misclassification and operator errors. Although histology is considered the gold standard to assign reproductive stages, it represents a time‐consuming and expensive method. Therefore, cost‐effective approaches are currently needed to assess the species‐specific reproductive potential and define the correct size at first maturity ( L 50 ). In the present study a histology‐calibrated method based on the gonadal index ( GI ) was developed to assign maturity stages to the overfished Mediterranean swordfish ( Xiphias gladius ), supported by histological classification of gonadal development, an estimation of L 50, and an analysis of the reproductive output of this species. The performance of this new method had an overall agreement of 90% with histological data, and the L 50 calculated by the GI ‐based method compared with histology analysis was not statistically different ( p  > 0.05). Moreover, in order to apply this method without bias, a thorough validation of the relationship between length and gonad weight was carried out and the suitability of the GI to compare individuals of different size and maturity stages was confirmed. The present findings provide a comprehensive picture of the patterns characterizing Mediterranean swordfish reproduction and a promising method to assign maturity stages based on a macroscopic indicator. This method has the potential to be extensively applied during routine fish sampling activities in the field because of its simple requirements.